Co-dynamics of climate policy stringency and public support. (May 2022) - Konc, Théo; Drews, Stefan; Savin, Ivan; van den Bergh, Jeroen C.J.M.
Highlights: Carbon tax with progressive recycling is the climate policy with highest support. Opinion stability affects the preferred policy trajectory. Social influence affects the preferred climate policy. Welfare-maximizing policies do not necessarily gather highest public support. Abstract: Public support for stringent climate policies is currently weak. We develop a model to study the dynamics of public support for climate policies. It comprises three interconnected modules: one calculates policy impacts; a second translates these into policy support mediated by social influence; and a third represents the regulator adapting policy stringency depending on public support. The model combines general-equilibrium and agent-based elements and is empirically grounded in a household survey, which allows quantifying policy support as a function of effectiveness, personal wellbeing and distributional effects. We apply our approach to compare two policy instruments, namely carbon taxation and performance standards, and identify intertemporal trajectories that meet the climate target and count on sufficient public support. Our results highlight the importance of social influence, opinion stability and income inequality for public support of climate policies. Our model predicts that carbon taxation consistently generates more public support than standards. Finally, we show that under moderate social influence and income inequality, an increasing carbon tax trajectory combined with progressive revenue redistribution receives the highest average public support over time.